Are mental disorders brain disorders? - Jefferson, Anneli (New York: Routledge, 2022)
"The question of whether mental disorders are disorders of the brain is a long-running and controversial dispute within psychiatry, psychology and the philosophies of mind and psychology. While recent developments in neuroscience push for brain correlates for mental disorders, detractors argue that labelling mental disorders as brain disorders is reductive and can result in harmful social effects. This book brings a much-needed philosophical perspective to bear on this important question. Anneli Jefferson argues that while there is widespread agreement on paradigmatic cases of brain disorder such as stroke, Parkinson's and Alzheimer's dementia, there is far less clarity on what the general, defining characteristics of brain disorders are. She pinpoints different notions of brain disorder to show how what counts as dysfunctional at the level of the brain frequently depends on what counts as dysfunctional at the psychological level. On this notion of brain disorder, she argues, many of the consequences people often associate with the brain disorder label do not follow. She also explores the important practical question of how to deal with the fact that many people do draw unlicensed inferences about treatment, personal responsibility or etiology from the information that a condition is a brain disorder or involves brain dysfunction. Are Mental Disorders Brain Disorders? brings philosophical clarity to this important question and will be of interest to students and researchers in the philosophies of mind and psychology, philosophy of psychiatry, and conceptual issues in mental health"--
Keywords: Brain; Neurobehavioral disorders